Proses berpikir siswa dalam memecahkan masalah matematika berdasarkan teori Polya ditinjau dari adversity quotient - Umainah, Siti Para; Setyowati, Rina Dwi; Sugiyanti, Sugiyanti (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This study aims to determine the thinking process of class X high school students in solving mathematical problems based on Polya’s theory in terms of adversity quotient. This research is a qualitative descriptive study. The subject of the study was the tenth grade students of SMA Negeri 1 Juwana consisting of only three students. Subject selection criteria are based on the type of adversity quotient (AQ), namely climber, camper, quitter and fluency when communicating (oral and written). The instruments used in the study were ARP (Questionnaire Response Profile), problem solving ability tests and interview guidelines. The validity of the data uses triangulation methods that compare the results of information obtained from written tests and interviews. The results of students’ thought processes in solving mathematical problems based on Polya’s theory in terms of the adversity quotient are as follows: 1) Students with AQ Climber do the assimilation thinking process in understanding the problem. Students perform the assimilationist thought process in compiling a completion plan. In solving problems students carry out the process of thinking assimilation and accommodation. And in re-checking the results obtained, students carry out the process of thinking assimilation and accommodation. 2) Students with AQ Camper do the accommodation thinking process in understanding the problem. Students perform the assimilationist thought process in compiling a completion plan. In solving problems, students carry out accommodation thinking processes. And in re-checking the results obtained, students do the accommodation thinking process. 3) Students with AQ Quitter do the assimilationist thought process in understanding the problem. Students do not carry out the process of thinking assimilation and accommodation in preparing a completion plan. In solving problems, students do not carry out the process of thinking assimilation and accommodation. And in re-checking the results obtained, students do not carry out the process of thinking assimilation and accommodation.